'Let me move to another level': career advancement desires and opportunities for community health nurses in Ghana. (June 2022) - Bellerose, Meghan; Awoonor-Williams, Koku; Alva, Soumya; Magalona, Sophia; Sacks, Emma
Career advancement and continued education are critical components of health worker motivation and retention. Continuous advancement also builds health system capacity by ensuring that leaders are those with experience and strong performance records. To understand more about the satisfaction, desires, and career opportunities available to community health nurses (CHNs) in Ghana, we conducted 29 in-depth interviews and four focus group discussions across five predominantly rural districts. Interview transcripts and summary notes were coded in NVivo based on pre-defined and emergent codes using thematic content analysis. Frustration with existing opportunities for career advancement and continued education emerged as key themes. Overall, the CHNs desired greater opportunities for career development, as most aspired to return to school to pursue higher-level health positions. While workshops were available to improve CHNs knowledge and skills, they were infrequent and irregular. CHNs wanted greater recognition for their work experience in the form of respect from leaders within the Ghana Health System and credit towards future degree programs. CHNs are part of a rapidly expanding cadre of salaried community-based workers in sub-Saharan Africa, and information about their experiences and needs can be used to shape future health policy and program planning.